Gender-based violence and associated factors during armed conflict among female high school students in Kobo town, North Wollo, Ethiopia: a facility-based cross-sectional study - Moges Wubie Aycheh; Gezahegn Aychew Andargie; Baye Tsegaye Amlak; Genet Degu Alamneh (BMJ Open)
Objective This study aimed to assess gender-based violence and associated factors during the time of armed conflict among female high school students in Kobo administration town, North Wollo, Ethiopia.Study design An institutional-based, quantitative and cross-sectional study was conducted.Setting This research was carried out in Kobo town, North Wollo, Ethiopia high schools.Study participants This study was conducted among 422 female high school students in Kobo administration town at time of armed conflict from May 20 to 5 June 2022.Outcome measures Gender-based violence (GBV) was assessed using a self-administered questionnaire. Data were entered in Epidemiological data (EPI-Data) V.3.1 and exported to SPSS V.25 for analysis. A binary logistic regression model was used to identify significant factors associated with GBV.Results The magnitude of GBV among female high school students at Kobo town during armed conflict was 45%, with 95% CI 40.2% to 49.8%. Students with poor current academic performance (Adjusted Odds Ratio (AOR)=3.001; 95% CI 1.335 to 6.750), students with a family member who participated in conflict (AOR=1.809; 95% CI 1.135 to 2.882), students with a family member who was subjected to conflict (AOR=1.954; 95% CI 1.164 to 3.281), students who drank alcohol (AOR=8.158; 95% CI 4.325 to 15.386) and students who did not freely disclosing reproductive health issues (AOR=3.267; 95% CI 1.509 to 7.075) were more likely to suffer GBV.Conclusions The magnitude of GBV during the armed conflict was high. Variables such as poor academic performance, family members who participated in the war, family members subjected to the war, students who drank alcohol and not freely discussing reproductive health issues were statistically associated with GBV. It is recommended to put in place programmes that address factors such as academic challenges, alcohol use, family trauma and the need for open discussions on reproductive health to help to reduce GBV.